Improving Skills Through Training in Freshwater Fish Farming and Crystal Guava Jam Production (Bantarjaya Village, Bogor Regency, West Java) - Umar, Ali; Risdiyanto, Idung; Albarkah, Anita Maharani; Aziz, Maulana; Bagaskara, Muhammad Fajar (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Fish farming is a type of fishing that involves cultivating various fish on land. Fish farming success can be influenced by site characteristics, water quality, fish suitability, and care. Crystal guava processing is a production utilization innovation. This has the potential to raise the value of crystal guava commodities, which can be consumed directly but are also processed into various derivative products. The community groups will be divided into two foster groups: the MSME group that makes crystal guava jam and the foster group that grows fish in irrigation ponds. This empowerment approach involves the creation of supporting infrastructure such as ponds in irrigation canals and the production of crystal guava jam. Then, using the t-test on the dependent mean and Principal Component Analysis, integrated training was carried out, including socializing and field practice, to quantify statistical development in abilities. As a result, the target community's understanding has increased. The target group (community) can increase their abilities in fish cultivation, the production of novel products (commodity derivatives), and marketing across various phases with the creation of supporting infrastructure.